A Proposal for a Mastology Post-Graduate Course for General Medicine Specialists - Lidia Torres Ajá; Miriam Iglesias León (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: Through a research conducted in the province of Cienfuegos the need for updating the general medicine specialists on early diagnosis of breast cancer as part of comprehensive care for women was confirmed. Objective: To design a post-graduate course on Mastology for general medicine specialists. Methods: Educational research conducted in the province of Cienfuegos, addressed to the methodological conception of a post-graduate course on mastology. Pertinence, relevance, characterization and objectives of this course are described, as well as the literature to be used. Results: A post-graduate course for general medicine specialists was designed. It was entitled "Updating of breast diseases" and consists of 3 classes (theoretical updating, breast imaginology tests, and practical training in mastology consultations and operation rooms) lasting 284 hours and providing 23 academic credits. Conclusions: The design and implementation of a post-graduate course including content on breast diseases will enable an early diagnosis of breast cancer, thus improving the quality of comprehensive care for women